PERAMALAN SUHU UDARA RATA-RATA DI KOTA MATARAM MENGGUNAKAN METODE LEAST SQUARE - Putri Amalia Wardani; Erin Anaras; Dewi Astuti; Nuzla Af’idatur Robbaniyyah; Tri Maryono Rusadi (Universitas Negeri Surabaya, 2025)
This study focuses on forecasting the average air temperature in the city of Mataram by applying the Least Square method to determine data patterns based on historical data. The data used includes the average air temperature from 2019 to 2023, obtained from the BPS Mataram City. Based on the pattern used, the resulting forecasting model for the average air temperature is Ŷ = 27.44 - 0.143X. The forecasted results indicate a gradual decrease in the average air temperature from 2024 to 2030 in Mataram. This trend is reflected by the change in the forecasted average air temperature value in the model, with a rate of -0.143. The model's accuracy is demonstrated by a Mean Absolute Percentage Error (MAPE) of 3.22%, indicating a very good level of accuracy in forecasting the average air temperature for the predicted years. This research is expected to provide useful information for the community and relevant stakeholders in Mataram to anticipate temperature changes and to plan for better climate adaptation policies in the future.